2011
DOI: 10.1101/lm.023887.111
|View full text |Cite
|
Sign up to set email alerts
|

Anterior thalamic lesions alter both hippocampal-dependent behavior and hippocampal acetylcholine release in the rat

Abstract: The anterior thalamic nuclei (ATN) are important for learning and memory as damage to this region produces a persistent amnestic syndrome. Dense connections between the ATN and the hippocampus exist, and importantly, damage to the ATN can impair hippocampal functioning. Acetylcholine (ACh) is a key neurotransmitter in the hippocampus, and in vivo measures of ACh are correlated to learning and memory performance. In the present study, complete lesions of the ATN impaired performance on two measures of hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 56 publications
(68 reference statements)
0
25
0
Order By: Relevance
“…* P < 0.05, ** P < 0.01 significant difference from the disease control group. the arms entry [72]. In RA test the measured parameters were WR and CR.…”
Section: Discussionmentioning
confidence: 99%
“…* P < 0.05, ** P < 0.01 significant difference from the disease control group. the arms entry [72]. In RA test the measured parameters were WR and CR.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that AT lesions in rats affect T-maze, plus-maze, and radial arm maze measures of allocentric spatial memory that depend on hippocampal function (Aggleton et al, 1996;Aggleton and Nelson, 2014;Dumont and Aggleton, 2013;Mair et al, 2003;Savage et al, 2011;Sziklas and Petrides, 2007). Indeed, Dalyrmple-Alford (2005, 2006) have provided direct evidence that AT lesions have greater effects than IL lesions on radial maze spatial memory tasks (but see Mair et al, 1998).…”
Section: The Anterior Nucleimentioning
confidence: 95%
“…The anterior, midline, intralaminar and mediodorsal nuclei are primary candidates for this association (Carlesimo et al, 2011; De Witte et al, 2011; Van Der Werf et al, 2003a). In rats, lesions of anterior thalamic nuclei produce deficits on a variety of learning and memory tasks, all of which are also affected by hippocampal lesions (Aggleton and Brown, 1999; Aggleton et al, 2010; Bailey and Mair, 2005; Gibb et al, 2006; Gold and Squire, 2006; Mair et al, 2003; Mitchell and Dalrymple-Alford, 2005, 2006; Moreau et al, 2013; Savage et al, 2011; Warburton et al, 2001; Wolff et al, 2006, 2008). For example, Lopez et al (2009) recently demonstrated that fiber-sparing excitotoxic lesions of the intralaminar nuclei in rats influence the consolidation/retrieval of remote (at 25 days), but not recent (at 5 days), spatial memory.…”
Section: Introductionmentioning
confidence: 99%